STRUKTUR CERITA WEJANGAN ANEH - A. Aisyah (Universitas Negeri Makassar, 2012)
This study aimed to describe the composition of Wejangan Aneh story. Research data was sourced from Fajar daily newspaper in Makasssar. Data analysis was done by using critical discourse analysis approach. The results showed that the beliefs of the people about supernatural, which represented by the use of the macro-structure and micro-structure. The central theme of the story is the emergence of the negative cultural ideology. That is the behavior of the villagers who liked to accept foreign cultures that caused negative impact and sin because they missed the attention of doing their worship.